Sustainable Development for the Healthcare Industry : Reprogramming the Healthcare Value Chain - Morgon, Pierre A. (Perspectives on Sustainable Growth, 2015)
This volume addresses the dynamics of sustainable development in the healthcare industry, covering all major aspects of the industry, including R&D, manufacturing, regulation, market access, commercialization, and general management.  Healthcare markets are evolving under demographic and economic pressures. In mature markets, patients navigate highly complex provider and cash-strapped payer systems with limited control on healthcare quality and outcomes (as reflected by the absence of correlation between spending and patient satisfaction and outcomes). In developing markets, patients have limited awareness, access and ability to pay for healthcare. The pools of profit will progressively shift from prescription drugs to other product segments and to healthcare delivery, and these shifts will be different by region. As it is dealing with a R&D drought, a revenues deflation induced by patient expiries affecting primary care franchises, a portfolio mix evolution towards specialty care products designed for highly profiled patient populations and backed by complex scientific and medical data, the industry needs to identify which business targets are genuinely attractive for major or new investments.   At the same time, development of new products and services must be tackled within the context of environmental sustainability.  Rather than focusing on the traditional issues of innovation, cost management, and commercial effectiveness associated with growth, the authors-including leading academics and industry insiders-explore such emerging topics as: The mutations of the management of innovation, as it remains the DNA of the healthcare industry, driven by patient focus and the trend towards personalized medicine the need to foster patient-centricity along the entire value chain of the healthcare industry and company-wide, starting by listening to the voice of the patient earlier in the lifecycle of drug candidates the broad scope of issues related to improving access to care and disease management, from drug design, to innovative licensing, to valuation based on real-world evidence, to supply and availability so as to ensure optimal access the allocation of educational resources focused on the patient to increase the effectiveness of disease management the preservation of natural resources and the environmental effects of pollution and hazards created by the handling of pharmaceutical products the capacity issues in relation to the size of the medical need and/or of the market demand the private-public partnerships to address the full spectrum of public health issues, from basic patient access to care to managing global health crises, the required organizational and governance evolutions for the healthcare industry to maintain profitable and sustainable growth.   Emphasizing environmental, economically, and socially sustainable practices, the authors present a unique, multi-faceted set of perspectives on this vital and rapidly evolving field. They provide a unique vantage point on the reboot the healthcare industry should engage into in order to enhance the sustainability of its business model.